A Digital Implementation of Eddystone Standard Using IBM 180nm Cell Library - Pereira, Rodrigo V.M.; Sousa, Fernando R. De; Bezerra, Eduardo A.; Berejuck, Marcelo D. (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2017)
Provided by Google, Eddystone standard consists of a beacon technology, open-source format, unidirectional and proximity-based Bluetooth® Low Energy (BLE) standard. Eddystone can support multiple different payloads, portable for IOS and Android with a ranging of approximately 50 meters. This paper analyses different metrics of a Verilog digital logical implementation of a Google Eddystone Standard using IBM 180nm cell library technology. It is focused on three main approaches: (i) establishing a digital Eddystone architecture, (ii) implementing and simulating the proposed architecture and (iii) performing a logical synthesis for future full-scale IC integration. Results show that by using our approach and requirements; the proposed architecture is suitable for integration with BLE analog/AMS front-end.